Dramatyczne przestrzenie Andrzeja Wajdy - Krajewska, Anna (Przestrzenie Teorii, 2017)
This editorial is an impressionistic work on Andrzej Wajda’s output, predominantly emphasising its dramatic nature. The text presents the uniqueness of Andrzej Wajda’s creative work in such diverse forms of art as if they were one – his painting metamorphosed into film, drawing into screenplay, urban space into a theatre stage. Wajda is seen here not only as a director, but also as a contemporary dramatist, who creates the dramatic space of history’s traps, who dramatises the fate of the individual, and who interprets the drama of the philosophical stage.